SINTESIS DIASETIL GAMAVUTON-0 DENGAN MENGGUNAKAN ASETIL KLORIDA SEBAGAI ACYLATING AGENT - Ridho Nugroho Zendrato; Supardjan Amir Margono (Universitas Islam Indonesia, 2005)
ABSTRACTGamavuton-0 is a curcumin-like compound, which is more stable than curcumin and stillhas an antioxidant property. The objective of synthesis of diacetyl gamavuton-0 (diAcGVT-0) is toyield the product that is more lipophile than GVT-0. Synthesis of diAcGVT-0 has been done byreacting GVT-0 with acetyl chloride as an acylating agent and tertiary amines as primary bases.DiAcGVT-0 was formed as the major product of synthesis and the product was not pure. Structureelucidation using UV-Vis,1H-NMR and MS spectra showed that the main product was diAcGVT-0.Key words : diacetyl gamavuton-0, acetyl chloride, acylating agent, lipophile